2016
DOI: 10.1111/jan.13022
|View full text |Cite
|
Sign up to set email alerts
|

Experience of hypertensive patients with self‐management of health care

Abstract: This phenomenon has paths, actions and interactions. When patients discover that they have the disease and become aware of the disease process, they assume the identity of being hypertensive and become proactive in their health care and in living with their families and in communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…According to other research health awareness of adult hypertension clients is more common in women than men (Balduino, Mantovani, Lacerda, Marin, & Wal, 2016). This is in line with research in one puskesmas in Tangerang district conducted for 8 months found that 61.6% of puskesmas visitors were women (Rahmayanti, Sarah, & Ariguntar, 2016).…”
Section: Gendersupporting
confidence: 75%
“…According to other research health awareness of adult hypertension clients is more common in women than men (Balduino, Mantovani, Lacerda, Marin, & Wal, 2016). This is in line with research in one puskesmas in Tangerang district conducted for 8 months found that 61.6% of puskesmas visitors were women (Rahmayanti, Sarah, & Ariguntar, 2016).…”
Section: Gendersupporting
confidence: 75%
“…Hypertension is considered a serious and frequent source of morbidity and mortality [1]. Moreover, it is one of the most common chronic illnesses in the world [2]. In fact, it is the number one cause of mortality and the third most common cause of disability-adjusted life years [3].…”
Section: Introductionmentioning
confidence: 99%
“…(4) Thus, to successfully control hypertension, selfcare practices by the patient are needed, which are defined as the performance of activities by individuals for their own benefit, to maintain life, health and well-being. (5) When effectively performed, self-care helps to maintain structural and functional integrity, contributing to human development. (6) However, when self-care is not performed, self-care deficits arise, making the integration of the healthcare professional essential to make the patients aware of the need to adopt self-care practices, aiming to prevent complications and promote health.…”
Section: Introductionmentioning
confidence: 99%